Extensive Reading Principles Implementation: Pleasure vs Pressure - Wiwiet Eva Savitri; Utami Widiati; Nunung Suryati; Francisca Maria Ivone (Journal of Languages and Language Teaching, 2024)
Extensive reading (ER) should be implemented properly based on ER principles. The most known ER principles is ten ER principles proposed by Bamford and Day that are widely referred by ER practitioners around the globe. Unfortunately, these principles are not always implemented in ER classes, even in ELT study program in university. Related to it, ER classes in a university in Indonesia were reported to not conducted ER enthusiastically. It was suspected that it occurred because of lecturers’ confusion on what to do in their ER classes due to their insufficient comprehension of ER and its principles which eventually reduce pleasure which supposed to be existing in ER classes. Based on that suspicion, this study focused on investigating the lecturers’ familiarity on ER principles and the implementation of ER principles regarding the expectation to conduct pleasurable ER classes. The data were collected through in-dept interviews to lecturers and questionnaire to students. This study found that not all of the lecturers have adequate knowledge on ER principles which eventually hindered them to teach ER properly and pleasurably. It was also revealed that pressure was felt by both students and lecturers. The pressure increased when the ER involved rigid assignment and assessment.